1981
DOI: 10.1159/000137479
|View full text |Cite
|
Sign up to set email alerts
|

Anesthetic, Hypothermic, Myorelaxant and Anticonvulsant Effects of Synthetic Eugenol Derivatives and Natural Analogues

Abstract: Nine newly synthesized eugenol derivatives were investigated in rats or mice as to their anesthetic, hypothermic, myorelaxant and anticonvulsant effects. Additional pharmacological activity which appeared during the experiments is described. For comparative purposes, six naturally occurring eugenol analogues were included in the study. The results are further discussed as to possible structure-activity relationships between the test compounds and the four investigated effects.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
68
0
2

Year Published

2002
2002
2015
2015

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 119 publications
(71 citation statements)
references
References 12 publications
1
68
0
2
Order By: Relevance
“…Furthermore, in agreement with the mechanism of action of EOCn, 1,8-cineole was found to act by a non-opioid mechanism (18). Methyleugenol (19) and a-terpineol (20) have been reported to be central and peripheral neural depressants, respectively, which raises the suspicion that they might act as antinociceptive agents. For the other constituents we found no report in the literature on either antinociceptive or neural activity.…”
supporting
confidence: 62%
“…Furthermore, in agreement with the mechanism of action of EOCn, 1,8-cineole was found to act by a non-opioid mechanism (18). Methyleugenol (19) and a-terpineol (20) have been reported to be central and peripheral neural depressants, respectively, which raises the suspicion that they might act as antinociceptive agents. For the other constituents we found no report in the literature on either antinociceptive or neural activity.…”
supporting
confidence: 62%
“…was used as the reference drug. Results were analyzed by repeated measures ANOVA followed by SNK (Dallmeier & Carlini, 1981).…”
Section: Hypothermic Effectsmentioning
confidence: 99%
“…Pharmacological studies show that eugenol demonstrated anesthetic, hypothermic, muscle-relaxant, anti-stress, and anticonvulsant activities (Dallmeier & Carlini, 1981).…”
Section: Chemical Compositions Of Essential Oilmentioning
confidence: 99%